Effects of Body Weight on Ski Jumping Performances under the New FIS Rules - Oggiano, L.; Saetran, L. (The Engineering of sport 7, Volume 1, 2008)
Based on the results of several different experiments, it has been concluded that the weight of a ski Jumper is crucial in performing a long ski jump. In response to this conclusion, many of the best ski Jumpers in the world began dieting to reduce their weight, resulting in many underweight athletes and some incidents of anorexia. In order to deal with this problem the International Ski Federation (FIS) introduced a new rule where the ski length is determined by both the jumper's height and weight, An athlete with a Body Mass Index (BMI) of less than 20 must reduce the length of his or her skis. To evaluate the effect of the new rules a numerical and experimental investigation on the effects of the BMI on ski jumper's performances has been done. A numerical model has been built in order to evaluate the effects of BMI on the final speed in the in-run path. The numerical results obtained from the model match experimental data present in the literature. Experiments in the wind tunnel have been made in order to evaluate the aerodynamic forces acting on the ski jumper and on the skis during the flight path according to the new FIS rules. Experiments have been carried out on a doll mounted on a 6 components balance and different positions and ski length have been tested. The data acquired have been introduced into a numerical model and the final jump length has been then estimated. In conclusions it has been found out that the current FIS rules do reduce the problem addressed but experiments shows that it is still more advantageous to lose weight and consequently cut the skis, compared to gaining weight in order to keep the full ski length.